2021
DOI: 10.1038/s41467-021-21055-0
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating intrinsic contribution of d-orbital states to oxygen evolution electrocatalysis in oxides

Abstract: Although numerous studies on oxide catalysts for an efficient oxygen evolution reaction have been carried out to compare their catalytic performance and suggest new compositions, two significant constraints have been overlooked. One is the difference in electronic conduction behavior between catalysts (metallic versus insulating) and the other is the strong crystallographic surface orientation dependence of the catalysis in a crystal. Consequently, unless a comprehensive comparison of the oxygen-evolution cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 62 publications
0
44
0
Order By: Relevance
“…5c ), in which the catalysts containing paramagnetic Fe species (NiFe-CNG) show quite different DOS structures. Their spin-up and spin-down components around the Fermi level are strongly fluctuant after connecting with the bridging oxygen atoms, leading to remarkable electronic perturbation 69 . The above discussion implies that the synergistic effect of Ni and Fe through the presence of Fe-O-Ni bonds in NiFe-CNG is a key prerequisite for high OER activity 70 , 71 .…”
Section: Resultsmentioning
confidence: 99%
“…5c ), in which the catalysts containing paramagnetic Fe species (NiFe-CNG) show quite different DOS structures. Their spin-up and spin-down components around the Fermi level are strongly fluctuant after connecting with the bridging oxygen atoms, leading to remarkable electronic perturbation 69 . The above discussion implies that the synergistic effect of Ni and Fe through the presence of Fe-O-Ni bonds in NiFe-CNG is a key prerequisite for high OER activity 70 , 71 .…”
Section: Resultsmentioning
confidence: 99%
“…Yun and co-workers recently found that semiconducting LaCoO 3 has an intrinsic OER activity more than one order of magnitude higher than that of metallic LaNiO 3 , in contrast to previous reports. 154 The group of authors showed that misleading interpretations could be avoided by using very thin lms of the catalyst on conducting interlayer as samples.…”
Section: Descriptors For the Binding Strength Of The Intermediate Oxygen Adsorbates: The Number Of Electrons In The E G -Orbitals Of The mentioning
confidence: 99%
“…As all the thin films in this work were fabricated by a sol–gel process, 19 both amorphous and perovskite-type crystalline nickelates could be easily acquired by optimal control of annealing temperature. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6–11 One of the major directions to achieve better OER electrocatalysis in these oxide-based materials is searching for new transition-metal compositional combinations. 12–19 Since the initial milestone report in 1987 by Corrigan, 20 who demonstrated that Fe impurities dramatically boost the OER activity in Ni, a significant number of studies have been carried out in Ni- and Co-based oxides and hydroxides to elucidate the role of Fe and its neighboring atoms as active sites. 13,14,19,21–30 As specifically shown in layered (oxy)hydroxides, 21,22,25 notable examples reveal remarkable enhancement of more than an order of magnitude in OER activity via Fe addition.…”
Section: Introductionmentioning
confidence: 99%